Effect of feeder design on finishing pig growth performance - Rantanen, M.M.; Richert, B.T.; Goodband, Robert D.; Hines, Robert H.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of three hundred pigs (initial BW = 111.6 lb) was used in two identical 70-d growth trials to determine the effect of feeder design on finishing pig growth performance. Pigs were allotted by initial body weight and were assigned to pens with one of three different feeder designs. Five replications of each treatment were evaluated during the summer (July through September) and another five replications during winter months (November through January). All pigs were fed the same milo-soybean meal diet formulated to contain .65% lysine, .65% Ca, and .55% P and fed in meal form. Feeder design had no effect on average daily gain (ADG) or average daily feed intake (ADFI) of finishing pigs. Pigs fed from the wet/dry feeder had improved feed efficiency (F/G) compared to pigs fed from either of the dry feeders. Water disappearance was lower for the pigs eating from the wet/dry feeder. These results suggest that the use of a single-hole, wet/dry feeder for growing-finishing pigs improves F/G and reduces water wastage.
Keywords: Swine; Pigs; Feeders; Growth